Aquatic insect diversity of Costa Rica: state of knowledge - Springer Springer, Monika (2008)
Costa Rica hosts an extraordinarily high biodiversity and is among the best studied neotropical countries. Insects represent the most diverse group of organisms, not only in terrestrial but also in aquatic, especially freshwater, habitats. Among the most diverse aquatic insect orders are the Trichoptera, Diptera and Coleoptera; although Ephemeroptera can locally also be very abundant and diverse. In Costa Rica, the taxonomically best known orders of aquatic insects are the caddisflies (Trichoptera), dragonflies (Odonata) and stoneflies (Plecoptera) and within the Dipterans, groups of medical importance have received special attention. The interest in aquatic insects has been constantly growing in Costa Rica over the past 10 years, but scientific publications are widely dispersed and often difficult to locate. Due to the importance of aquatic organisms in environmental impact studies and biomonitoring of freshwater habitats, there is an urgent need for comprehensive studies and publications that are locally available. In this sense, the present paper tries to give an overview on the state of knowledge and the literature published to date on the aquatic insects of Costa Rica, taking in account taxonomic, biological and ecological studies.